Pelaksanaan Program Kegiatan Khitobah Bagi Siswa Kelas X di Smk Andalusia 1 Wonosobo Tahun Pelajaran 2022/2023 - Fahrunnisa Rahma Desylia; Maryono; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2023)
Students' lack of self-confidence makes it difficult for them to convey ideas, so they need to practice self-confidence, one of which is with Khitobah activities. The purpose of this study was to find out: (1) Implementation of the Khitobah Activity Program for Class X Students at SMK Andalusia 1 Wonosobo Academic Year 2022/2023. (2) the supporting and inhibiting factors for the implementation of the Khitobah activity program. (3) how is the evaluation of the implementation of the Khitobah activity for Class X Students at SMK Andalusia 1 Wonosobo. This type of qualitative descriptive research with data collection techniques through observation, interviews and documentation. The subjects of this study were students and teachers at SMK Andalusia I Wonosobo. The results of this study were; (1) The implementation of Khitobah for class X students at SMK Andalusia was planned and included scheduling, mentoring of Khitobah, Practice of Khitobah, and Evaluation of Khitobah. (2) Supporting factors and inhibiting factors in the implementation of khitobah. The supporting factors are as follows: (a) Internal factors: from within the students themselves because basically students have different motivations in participating in khitobah activities. (b) External Factors, including: Education, Training, Work, Environment, Habituation. (3) Evaluation of the implementation of khitobah begins with the teacher designing an assessment, which includes making schedules, khitobah materials, monitoring the implementation, evaluating the implementation and evaluating khitobah practices.